2017
DOI: 10.1038/s41598-017-10474-z
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged AT1R activation induces CaV1.2 channel internalization in rat cardiomyocytes

Abstract: The cardiac L-type calcium channel is a multi-subunit complex that requires co-assembling of the pore-forming subunit CaV1.2 with auxiliary subunits CaVα2δ and CaVβ. Its traffic has been shown to be controlled by these subunits and by the activation of various G-protein coupled receptors (GPCR). Here, we explore the consequences of the prolonged activation of angiotensin receptor type 1 (AT1R) over CaV1.2 channel trafficking. Bioluminescence Resonance Energy Transfer (BRET) assay between β-arrestin and L-type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 51 publications
0
17
0
Order By: Relevance
“…Synaptic boutons along neurites (10 mm starting from the cell body) were automatically counted using ImageJ (Esposito et al, 2019). The presynaptic localization of the L-type Ca 21 channel was analyzed in treated neurons by evaluating the immunoreactivity of L-type Ca 21 channel (1:200, Alomone Labs) (Hermosilla et al, 2017) in vGLUT1-positive excitatory boutons. The area of colocalization puncta and the percentage of colocalization were automatically evaluated using ImageJ.…”
Section: Methodsmentioning
confidence: 99%
“…Synaptic boutons along neurites (10 mm starting from the cell body) were automatically counted using ImageJ (Esposito et al, 2019). The presynaptic localization of the L-type Ca 21 channel was analyzed in treated neurons by evaluating the immunoreactivity of L-type Ca 21 channel (1:200, Alomone Labs) (Hermosilla et al, 2017) in vGLUT1-positive excitatory boutons. The area of colocalization puncta and the percentage of colocalization were automatically evaluated using ImageJ.…”
Section: Methodsmentioning
confidence: 99%
“…It has been increasingly recognized that heterodimerization of GPCRs could bias the signaling pathway of the partner receptor ( Ferre et al., 2014 ; Forrester et al., 2018 ). It has also been reported that ligand binding to GPCRs triggers signal transduction modified by interactions with non-GPCRs, such as ion channels ( Hermosilla et al., 2017 ; Shenoy and Lefkowitz, 2011 ; Shukla et al., 2010 ). However, our previous study is the only example of ligand binding to single transmembrane receptor-induced activation of an adjacent GPCR in the oligomeric complex ( Yamamoto et al., 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, sustained angiotensin II stimulation of angiotensin receptor type 1 (AT1R) on the Ca v 1.2 calcium channel induces β-arrestin 1 recruitment to the channel complex, causing the internalization of Ca v 1.2 in T-tubules. Therefore, L-type calcium currents decrease by ≈60%, and calcium transient amplitude and action potential duration decrease [ 91 ].…”
Section: The Components Of Ion Channel Endocytosismentioning
confidence: 99%